2020
DOI: 10.4269/ajtmh.19-0498
|View full text |Cite
|
Sign up to set email alerts
|

Complex Cytokine Responses in Imported Scrub Typhus Cases, Germany, 2010–2018

Abstract: Scrub typhus is a life-threatening zoonotic disease, which is caused by Orientia tsutsugamushi, an obligatory intracellular Gram-negative bacterium. It is transmitted by Leptotrombidium mites in endemic regions of Southeast Asia. So far, data on imported scrub typhus cases to non-endemic areas and immunological descriptions are rare. Eleven scrub typhus cases that had been diagnosed by the German National Reference Center for Tropical Pathogens between 2010 and 2018 were retrospectively reviewed for clinical s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Upon O . tsutsugamushi infection, a “cytokine storm” is known to occur in a subgroup of patients with scrub typhus [ 16 , 26 ] and may be associated with severe complications [ 14 , 15 , 27 ]. A number of studies reported that IL-6, IL-8 [ 14 ], IL-10 [ 15 ], MCP-1 [ 14 ], MIP-1β [ 14 ] and TNF [ 15 , 17 , 43 ] serum levels correlate with disease severity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Upon O . tsutsugamushi infection, a “cytokine storm” is known to occur in a subgroup of patients with scrub typhus [ 16 , 26 ] and may be associated with severe complications [ 14 , 15 , 27 ]. A number of studies reported that IL-6, IL-8 [ 14 ], IL-10 [ 15 ], MCP-1 [ 14 ], MIP-1β [ 14 ] and TNF [ 15 , 17 , 43 ] serum levels correlate with disease severity.…”
Section: Discussionmentioning
confidence: 99%
“…Intradermal inoculation of CD-1 Swiss outbred mice (closely mimicking the natural infection route) revealed that Karp and Gilliam strains led to more severe disease than Kato and Woods strains [13] and that the intracellular cytokine signatures induced by the intradermal inoculation of Karp and Woods strains (non-lethal scrub typhus models) differed significantly from that induced by the intraperitoneal inoculation of Karp strain (lethal scrub typhus model) [10]. Available data from mouse and human studies suggest that in severe scrub typhus with an overwhelming pathogen load, the host immune system produces a strong inflammatory cytokine response, which associates with increased disease severity and complications [10,[14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation